CORRELATION AMONG PREDICTED GENOTYPIC VALUES AND ADAPTABILITY AND STABILITY ESTIMATES OF SUGARCANE CLONES IN A MIXED MODELS CONTEXT - BARBOSA, Márcio Henrique Pereira; de RESENDE, Marcos Deon Vilela; PEDROZO, Cássia Ângela; MELO, Cristiane Gamarano; PETERNELLI, Luiz Alexandre; COSTA, Paulo Mafra de Almeida; XAVIER, Clariana Valadares; BAFFA, David Carlos Ferreira (Scientia Agraria, 2009)
The objective of the present study was to apply the mixed model theory to predict the genotypic values and to estimate the adaptability and stability parameters of sugarcane clones evaluated in augmented blocks designs in several environments and to assess the correlation among these predicted and estimated values. Methodologies by Wricke (Wricke & Webber, 1986), Eberhart & Russell (1966) and Carneiro (1998) were used. The predicted genotypic values free from genotype x environment interaction were strongly correlated with the parameters estimated by the Carneiro’s methodology, moderately correlated with adaptability parameter ( ) of Eberhart and Russel and weakly correlated with the Wricke ωi (%) parameter and with R2i (%) parameter of Eberhart and Russell. The Wricke ωi (%) parameter only presented significant correlation with the R2i (%) parameter of Eberhart and Russell, indicating the similarity of both in assessing the stability of genotypes. These results show that the predicted genotypic values free from genotype x environment interaction effects correlate better with adaptability than with stability.